2014
DOI: 10.4172/2157-7579.1000217
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feeding Dried Tomato Pomace and Concentrate Feed on Body Weight Change, Carcass Parameter and Economic Feasibility on Hararghe Highland Sheep, Eastern Ethiopia

Abstract: The study was conducted using 24 yearling intact Hararghe highland male sheep with mean initial body weight (BW) of 16.73 ± 2.47 kg (Mean ± SD), with the objectives to evaluate the effect of supplementation of dried tomato pomace, and concentrate feed on live weight gain, carcass characteristics and economic feasibility of the feeding regime of sheep fed a basal diet of natural pasture hay. The experiment consisted 90 days feeding and followed by evaluation of carcass parameters at the end. The animals were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
4
5
1
Order By: Relevance
“…Slaughter weight, EBW and HCW were lower (P<0.05) for T1 than all other treatments which did not significantly differ among each other (P>0.05), which is in line with [9]. Dressing percentage also took a similar trend like that of HCW.…”
Section: Carcass Componentsupporting
confidence: 67%
“…Slaughter weight, EBW and HCW were lower (P<0.05) for T1 than all other treatments which did not significantly differ among each other (P>0.05), which is in line with [9]. Dressing percentage also took a similar trend like that of HCW.…”
Section: Carcass Componentsupporting
confidence: 67%
“…Contrary to the present study, the ADG of sheep fed a diet based on SCB treated with brown rot fungi (Trichodermareessei F-418) was less than that of sheep fed a diet based on untreated SCB (El-Banna, Shalaby, et al, 2010), but FCE was increased for this group. Value of the present study also agrees with the value reported for the same breed at the maximum level of supplementation (Diba et al, 2015;Hirut et al, 2011;Kefyalew et al, 2015). Similarly, the result is comparable with the findings reported for Arsi-Bale sheep fed a basal diet of hay and supplemented with 300 g DM of sole or a mixture of linseed meal and wheat bran (Abebe et al, 2010).…”
Section: Performances Of Ramssupporting
confidence: 93%
“…(2017) , who reported higher body weight gain and feed conservesion efficiency for different Ethiopian sheep breeds consumed high crude protein in g/day and metabolizable energy in MJ/day as compared to those consumed lower crude protein and metabolizable energy. The average daily weight gain recorded for the RH diet group was higher than the values 32.2 g/d-63.2 g/d ( Hirut et al., 2011 ) and 30 g/d- 65 g/d ( Gebeyew et al., 2011 ) reported for the same breed fattened with diets based on different basal diets and at different levels of concentrate supplementation, these could be due to lower CP and ME intake by these group. The higher body weight gain and feed conversion efficiency (FCE) of the biologically treated by-products as compared to untreated is the result of improved feed utilization by treatments.…”
Section: Discussioncontrasting
confidence: 54%